PERAN ASSOCIATION INTERNATIONALE DES ÉTUDIANTS EN SCIENCES ÉCONOMIQUES ET COMMERCIALES (AIESEC) SEBAGAI AKTOR NON NEGARA DALAM MEMINIMALISIR DAMPAK ISU RASIAL PADA MASYARAKAT CINA TERHADAP INDONESIA PASCA KERUSUHAN MEI 1998 - Rhamadani, Rizka Dea (Global and Policy Journal of International Relations, 2015)
ABSTRACTBackground problem in this article are the presence of anti-Chinese negative view on Indonesian society, as a result of riots in 1998 in Indonesia. The background is then raises the question of the formulation of the problem in this research, namely the role of AIESEC in changing student views China as a representative of the Chinese people against Indonesia as a result of the riots in May 1998. This study uses the concept of global civil society to explain the organization AIESEC as part of a global civil society, as well as the theory of resource mobilization and new social movements which describes the actions of the organization. This study was taken from the years 2010 - 2015 when the state of the organization has had a good strategy, and the attempt of the state to press the issue of racism. From the formulation of the problem and the theories used the AIESEC role in minimizing the negative view is that the activities of social programs and social projects ambassador volunteer program run by AIESECKeywords : AIESEC, Global Civil Society, Sosial Project, Volunteer AmbassadorsDOI:https://doi.org/10.33005/jgp.v3i01.1959